2015
DOI: 10.4103/0976-237x.152935
|View full text |Cite
|
Sign up to set email alerts
|

Use of buccal myomucosal flap for palatal lengthening in cleft palate patient: Experience of 20 cases

Abstract: Background:The purpose of this review was to assess the effectiveness of the buccal myomucosal flap in secondary repairs of cleft palate in 20 patients.Patients and Methods:Totally, 20 patients, who underwent secondary palatoplasty between 5 years and 8 years in which a buccal myomucosal flap was used, were reviewed retrospectively. All patients had undergone at least one previous attempted repair at other institutions. Indications for the secondary repair included velopharyngeal incompetence and/or oronasal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
13
0
1
Order By: Relevance
“…However, minimal swelling and scarring would be seen in lasers due to healing by secondary intentions. This is also associated with tissue regenerations for new tissue formation on the involved areas [23][24][25]. Therefore, the laser technique provides better healing in comparison to the surgical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…However, minimal swelling and scarring would be seen in lasers due to healing by secondary intentions. This is also associated with tissue regenerations for new tissue formation on the involved areas [23][24][25]. Therefore, the laser technique provides better healing in comparison to the surgical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The use of potential periodontal biomarkers of healing such as fibroblast growth factor 2 levels, cathepsin levels, endothelin 1 levels could have been correlated to obtained findings. [21][22][23][24]The present study population was not homogenous and different treatment techniques were applied to different number of patients with no correlation to oral hygiene status of the patients…”
Section: Resultsmentioning
confidence: 99%
“…There was a postoperative fistula rate of 8.8% in patients with wide clefts who received BMFs compared to 1.2% in those with narrow clefts who received no BMFs (Mann et al, 2017). BMFs have also been previously applied to secondary palatoplasty (Nakakita et al, 1990; Hill et al, 2004; Varghese et al, 2015). While speech outcomes remain understudied, in 2004, Hill et al, reported improved speech outcomes at 6 months following the use of the BMFs as a “sandwich” for secondary palatal lengthening to address secondary velopharyngeal insufficiency (Hill et al, 2004).…”
Section: Discussionmentioning
confidence: 99%